PENINGKATAN PRODUKTIVITAS EMPING MLINJO MELALUI PENGEMBANGAN MESIN SANGRAI, WEB, DAN MANAJEMEN USAHA - Aan Ardian, Aman, Lia Yuliana, (Universitas Negeri Yogyakarta, 2014)
One of the flag ship products of Bantul area is a traditional foodproduct that is made from chips mlinjo based mlinjo. For rural areas,potential areas of Bantul strongly supports the development of traditionalfood craft industry mlinjo chips. Mlinjo plants are very easy to get inBantul. Melinjo kind of chips are made from fruit that has been melinjoold. Making chips is not difficult and can be done using simple tools.Mlinjo is one of the processing of agricultural commodity prices are high.These commodities can be exported to neighboring countries. But the factis lack of capital held, the lack of touch technology in the productionprocess, especially in the roaster mlinjo quickly, applied managementsystem is very simple, so profits and losses can not be detected properly,yet have the ability to use information technology can be used as amarketing medium.To achieve these objectives, the methods used in this activity is thecreation of training mlinjo roaster machine that can be adjusted as neededto improve the quality and quantity. Web design training to support themarketing of products crackers mlinjo, business management training. IbMSmall Industries Group activities Craftsmen Emping mlinjo in Beji,displays Bantul Yogyakarta for 3 days on 3, 4, and 5 November 2013at 07:30 to 16:30 pm. In general, all participants followed the eventswith high motivation and earnest. It is evident in their attendance on aregular basis for three days and follow each session with care andenthusiasm. The questions they launched during the opening session.Things are less clear they as to obtain understanding. The first day oftraining activities, participant follow carefully. They feel they havereceived during this new knowledge they do not know, the participantsbecame more familiar.Keywords: small industries group, emping mlinjo